The law of sentencing - Manson, Allan (Irwin Law, 2001)
"The Law of Sentencing by Allan Manson is intended to provide a summary of the legal principles and rules that shape the current process of sentencing in Canada. The book will appeal to seasoned practitioners and law students alike., Following a discussion of the historical and philosophical context in which sentencing occurs, the book then examines the decision-making methodology, particularly the relevant rules and principles that the judiciary applies when sentencing offenders. It explains the structure and procedure of the sentence hearing and provides a detailed account of all available sentencing options. Separate attention is paid to the specific issues of sentencing in homicide cases, and preventative detention. Finally it examines the appeal process and the role of appellate courts., The book includes a postscript on the Supreme Court of Canada decision in R v. Latimer."–Pub. desc.